Strategic personal branding in the creative economy: A case study of indonesian musician repositioning through instagram - Past Novel Larasaty; Widya Putri, Dhita; Dinda Hayatin Nuppus (Economica, 2026)
This study investigates the strategic significance of personal branding within the creative economy by analyzing the digital rebranding of an Indonesian artist on Instagram. It examines the role of consistent visual identity, authenticity, and value-driven content in enhancing audience engagement and fortifying brand equity over time. The findings, derived from a qualitative descriptive method utilizing in-depth interviews and content analysis, indicate that personal branding serves both as a communication tool and a business strategy that improves visibility, revenue potential, and career sustainability. The research highlights Instagram's efficacy as a medium for musicians to convey their artistic development and social identity. This research elucidates how creative professionals utilize digital media for strategic repositioning in a competitive cultural market, providing valuable insights for academic inquiry and practical applications in digital branding.